Effect of Work Environment and Discipline on Organizational Commitment to BPJS Employment (Case Study of BPJS Employment Branch Medan Utara) - Siti Hazrah; Wahyu Syarvina (Journal of Indonesian Management, 2022)
Among the factors affecting low productivity are work discipline and occupational supervision. Job discipline is a vital force for a company to achieve its goals. In the process, companies should also be able to implement optimal surveillance. The study aims to know the effect of job discipline and occupational supervision on worker productivity on the northern field branch work. Then the purpose went on to know the effects of work discipline and collective supervision on worker labor productivity on the northern field branch work